Development and coupling test of active spacecraft potential control – Next generation (ASPOC-NG). Issue 3 (1st February 2023) - Mühlich, Nina Sarah; Jeszenszky, Harald; Fries, Johanna; Fremuth, Gerhard; Gerger, Joachim; Plesescu, Florin; Steller, Manfred; Seifert, Bernhard; Nakamura, Rumi; Cipriani, Fabrice
Highlights: Development of next generation of active spacecraft potential control (ASPOC-NG). One instrument for positive and negative spacecraft charge compensation. Coupling test of ASPOC-NG instrument, including accuracy and lifetime test. Low resource potential control device as candidate for future science missions. Abstract: The active spacecraft potential control (ASPOC) system developed in the 1990s emits positive ions to neutralise the spacecraft potential, such as used in several missions like Geotail, Equator-S, Cluster, Doublestar and MMS. With the experience gained, the next generation of the active spacecraft potential control (ASPOC-NG) instrument has been developed over the last three years. Thereby, three emission technologies were tested including Liquid Metal Ion Source (LMIS), Liquid Metal Electron Source (LMES) and Solid Metal Electron Source (SMES). The development of the emitter module by FOTEC and the corresponding electronics control unit by IWF is presented. Optimisations were carried out with the focus on the reduction of mass and power consumption to comply with the requirements of future scientific missions. Coupling tests of the modules and the electronics control unit were performed including range, accuracy and lifetime tests. Both ASPOC-NG instruments for positive and negative charge compensation and their performance values show excellent results.